Spiritualisme dan Pluralisme dalam Masyarakat Modern - Aulia Rosa Nasution; Anwar Hulaifi (Journal of Mandalika Literature, 2024)
Spiritualism and pluralism are two different things but are related to one another. In spiritualism, the soul or spirit becomes a supporting medium for the existence of spiritualism by believing in God as the creator of the entire universe which causes the emergence of a relationship between humans and their God. Pluralism prioritizes diversity and differences in various aspects of society's life. This study will highlight the two objects, namely spiritualism and pluralism as a reality in modern and complex societal life. The results of this study show that the role of spiritualism and pluralism can be a solution in resolving conflicts between modern and complex societies by implementing them based on spiritual values which are based on belief in the Almighty God and pluralism values which respect differences in society and at the same time become a filter for various challenges in the life of a pluralistic society.